2006
DOI: 10.1080/00016350600788245
|View full text |Cite
|
Sign up to set email alerts
|

Flowable resin composite as a class II restorative in primary molars: A two-year clinical evaluation

Abstract: Vitremer and Tetric Flow showed no significant difference concerning clinical durability at 2 years when used as class II restoratives in primary molars. Both materials demonstrated acceptable clinical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Since there was no randomized clinical trial comparing GIC and CR restorations, indirect comparisons by means of a mixed treatment comparisons meta-analysis were carried out. The pair-wise comparisons of GIC vs. RMGIC 21 and CR vs. RMGIC 19,20 showed higher risk of failure for GIC compared to CR. This finding is in line with a retrospective study with 4 years of follow-up that found that CR restorations in primary teeth presented lower failure rate than GIC ones.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since there was no randomized clinical trial comparing GIC and CR restorations, indirect comparisons by means of a mixed treatment comparisons meta-analysis were carried out. The pair-wise comparisons of GIC vs. RMGIC 21 and CR vs. RMGIC 19,20 showed higher risk of failure for GIC compared to CR. This finding is in line with a retrospective study with 4 years of follow-up that found that CR restorations in primary teeth presented lower failure rate than GIC ones.…”
Section: Discussionmentioning
confidence: 99%
“…There were six RCTs using parallel groups, 15,16,17,18,19,20 one RCT 21 using split-mouth design in most samples and ten RCTs using split-mouth for all samples. 14,22,23,24,25,26,27,28,29,30 The follow-up period ranged from 12 to 60 months; however, 47.06% of the studies had 24 months of follow-up.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of the 4 restorative intervention studies assessed permanent dentition caries 1,3 ; 2 assessed primary dentition caries. 2,4 …”
Section: Main Outcome Measurementioning
confidence: 99%